A Review of the Issues by Which a Blockchain Solution Could Improve the Prevailing Healthcare Paradigm: A Review of the Issues by Which a Blockchain Solution Could Improve the Prevailing Healthcare Paradigm - Ewing, Graham Wilfred (Asian Journal of Computer Science Engineering(AJCSE), 2019)
Blockchain, as applied to the health-care domain, is currently a dream or vision of what people want to happen. There are few technologies which offer the potential to disrupt the prevailing biomedical paradigm. The author discusses the existence of the first technology to be based on a precise and sophisticated simulation of how the brain regulates the autonomic nervous system and associated structures which has the potential to significantly disrupt the prevailing biomedical paradigm through the emergent neurological paradigm, i.e., understanding how the brain works and how this can be applied with diagnostic and/or therapeutic effect. Known commonly by the trade name â€œStrannikâ€ the associated package of Strannik software programs have been shown in initial research, in 15â€“20 clinical studies conducted over the period 1997â€“2017, that Strannik Virtual Scanning is able to determine the onset and progression of pathologies 2â€“23% more accurately than the current plethora of medical tests; screen pathological onset from the presymptomatic level; define each pathology in terms of its genotype and phenotype; determine ca. 5â€“15 pathologies are determined in each of 30+ organs, provide results in ca. 10â€“15 min; more safely/non-invasively than contemporary methods of diagnosing and treating disease; achieve therapeutic outcomes with the neuromodulation technique strannik light therapy which initial studies indicate is 75â€“96% therapeutic effectiveness i.e., which appear to exceed that which is possible using biomedicine; and to do as at considerably lower cost by comparison with biomedical tests and treatments. The author discusses the limitations of biomedicine and how such a neurological approach, in the form of the Strannik technology, could be applied to address such limitations and provide an alternative and cost-effective approach to the provision of health care, in particular (but not exclusively), regarding the management of lifestyle-related medical conditions.